Molecular Docking, Pharmacokinetics, and Toxicity Prediction of Epigallocatechin-3-Gallate (EGCG) on IKK Receptor in Photoaging Prevention - Damayanti1,2, Cita Rosita Sigit Prsakoeswa2, Djoko Agus Purwanto3, Anang Endaryanto4, Siswandono3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Photoaging is skin aging, caused by chronic exposure of ultraviolet radiation. Photoaging decreases patients’ quality of life because the skin was the outer organ seen by others. Ultraviolet radiation causes oxidative stress, that activated inhibitory kappa B kinase (IKK), increased nuclear factor kappa B (NF-kB), matrix metalloproteinase (MMP), and degradation of collagen. Epigallocatechin-3-gallate (EGCG) was the main green tea polyphenol and the main source of biologic activity of green tea. This study was an in silico study, aimed to obtain the effectiveness of EGCG component through molecular docking on IKK receptor (PDB ID: 5EBZ). The bioinformatics tools based on reverse docking used in this study, were Protein Data Bank, ChemDraw, Chem3D, and Molegro Virtual Docker software. Docking and binding site analysis showed, that EGCG was able to interact with IKK receptor. Rerank score of interaction between EGCG and IKK receptor was higher than that of arbutin and 5TL_701[A]. It showed that EGCG has higher potential in photoaging prevention than arbutin, as one of the agents in photoaging prevention. Pharmacokinetics and toxicity (ADMET) prediction in this in silico study were conducted using pkCSM On Line tool. The pkCSM results showed EGCG was predicted having good pharmacokinetics profile without toxicity effect.